2018
DOI: 10.24275/uam/azc/dcsh/ae/2018v33n83/sosa
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Linkages between Stock Market and Exchange Rate in mila Countries: A Markov Regime Switching Approach (2003-2016)

Abstract: This paper aims to analyse the dynamic relationship between the stock market returns and exchange rates movements for the mila (Mercado Integrado Latinoamericano) countries: Colombia, Chile, México and Peru, over the period 01:2003 to 09:2016. Univariate (Markov Switching-Autoregressive) and multivariate (Markov Switching-Vector Autoregressive) regime-switching models approach are used. The univariate analysis offers evidence indicating that stock returns of the mila countries evolve according to two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 15 publications
5
21
0
4
Order By: Relevance
“…) in this number of iteration or step (i), the analyst returns to the first stage in the estimation algorithm, as this set is the new prior. Then, she updates the filtered probabilities, Equation (6) or Equation (7), with the new parameter set, (θ i ), calculates the LLF i with Equation (8), and updates, with Equations ( 9) to (11), the parameter set with the new filtered probabilities. This numerical method continues until the LLF i values between the current iteration (i) and the previous one (i − 1) have a difference lower than a δ threshold value…”
Section: The Rationale Behind Ms and Ms-garch Models The Input Data Processing Method And The Trading Strategy Simulation's Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…) in this number of iteration or step (i), the analyst returns to the first stage in the estimation algorithm, as this set is the new prior. Then, she updates the filtered probabilities, Equation (6) or Equation (7), with the new parameter set, (θ i ), calculates the LLF i with Equation (8), and updates, with Equations ( 9) to (11), the parameter set with the new filtered probabilities. This numerical method continues until the LLF i values between the current iteration (i) and the previous one (i − 1) have a difference lower than a δ threshold value…”
Section: The Rationale Behind Ms and Ms-garch Models The Input Data Processing Method And The Trading Strategy Simulation's Parametersmentioning
confidence: 99%
“…Other papers test the spillover effect between stock and currency markets of developed and developing countries. Examples of these are the works of Mouratidis et al [43], Miles and Vijverberg [44], Lopes and Nunes [45], Kanas [46], Álvarez-Plata and Schrooten [47], Parikakis and Merika [48], Girdzijauskas [49], Dubinskas and Stungurienė [50], Kutty [51], Ahmed et al [52], and Sosa, Ortiz, and Cabello [11].…”
Section: Literature Review Of the Use Of Ms-garch Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the model in the U.S., the U.K., Brazil, and South Korea, they found that their model was appropriate to model the volatility clustering effect, due to the time-varying properties of the correlation among markets, but also given their tested regime-switching framework. With respect to emerging stock markets, we mention the works of Cabrera et al [47] and Sosa, Ortiz and Cabello [48] who tested the use of either MS or MSGARCH models in Latin American stock markets. Their results were in agreement in that it was appropriate to use either two regime MS models [48] or three regime MSGARCH models [47] in order to characterize the performance of these markets.…”
Section: Review Of the Previous Literature That Motivates Our Testsmentioning
confidence: 99%
“…With respect to emerging stock markets, we mention the works of Cabrera et al [47] and Sosa, Ortiz and Cabello [48] who tested the use of either MS or MSGARCH models in Latin American stock markets. Their results were in agreement in that it was appropriate to use either two regime MS models [48] or three regime MSGARCH models [47] in order to characterize the performance of these markets. In addition, they suggested that these models could be useful to measure the spillover effect and the potential presence of a "Latin American stock market common cycle".…”
Section: Review Of the Previous Literature That Motivates Our Testsmentioning
confidence: 99%